Cathelicidin bovine myeloid antimicrobial peptide (BMAP) 28 is involved in the inflammatory response against alpha-herpesviruses in the bovine nervous system - Burucúa, Mercedes María; Perez, Sandra; Odeon, Anselmo Carlos; Cobo, Eduardo Ruben; Quintana, Silvina; Marin, Maia Solange (Elsevier, 2020)
The role of the local innate immune response in the neuropathogenesis of bovine herpesvirus (BoHV) type 1 and 5 remains largely unknown. This study determined the gene transcriptional expression of relevant bovine cathelicidins, TNFα and IFNβ in the nervous system of experimentally-infected cattle during the different stages of BoHV-1 and BoHV-5 infectious cycle. We studied the modulation of bovine myeloid antimicrobial peptide (BMAP) 27 and 28 by alpha-herpesviruses during acute infection of the central nervous system (CNS). However, BMAP 28 was the main cathelicidin modulated.. BoHV-5 supressed BMAP28 expression mainly in frontal cortex and cervical medulla whereas BoHV-1 slightly induced the expression of cathelicidins in the olfactory and posterior cortex. The differences in the regulation of the innate response are likely related to distinct replication rates of both alpha-herpesviruses in the CNS. During latency and reactivation, BoHV-1 and -5 decreased BMAP28 and BMAP27 expression, accompanied by high levels of TNFα and IFNβ transcripts in the posterior brain region and medulla during BoHV reactivation. In terms of cytokines, a remarkably overexpression of IFNβ was induced by BoHV-5 (133.8-fold). In trigeminal ganglion (TG) both alpha-herpesviruses induced cathelidicins gene expression at all stages of the infection cycle, while only acute BoHV-5 infection increased TNFα (129-fold) mRNA levels. This study suggests that the pronounced downregulation of BMAP28 in BoHV-5-acutely-infected CNS is due to a decreased immune stimulation during viral infection, favouring its establishment in the CNS with a low replication rate until latency. Thus, cathelicidins, together with IFNβ and TNFα, are differentially regulated by BoHV-5 and BoHV-1 infections and this regulation is dependent on the stage of virus infection in the bovine nervous system.